Epithelial-mesenchymal transformation of embryonic cardiac endothelial cells is inhibited by a modified antisense oligodeoxynucleotide to transforming growth factor beta 3. - Potts, J D (1991)
During early cardiac development, the progenitor cells of the heart valves and membranous septa undergo an epithelial-mesenchymal transformation. Previous studies have shown that this transformation depends on the activity of a transforming growth factor beta (TGF beta) molecule produced by the heart. In the present study, we have used modified antisense oligodeoxynucleotides generated to nonconserved regions of TGF beta 1, -2, -3, and -4 to examine the possible roles of these members in this transformation. A phosphoramidate-modified oligonucleotide complementary to TGF beta 3 mRNA was capable of inhibiting normal epithelial-mesenchymal transformation by 80%. Unmodified oligonucleotides to TGF beta 3, modified oligonucleotides to TGF beta 1, -2, and -4, and two modified control oligonucleotides were unable to inhibit the transformation. These data demonstrate that a specific member of the TGF beta family, TGF beta 3, is essential for the epithelial-mesenchymal cell transformation.